2023
DOI: 10.1017/jns.2023.11
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and intuitive eating: an emerging approach to eating behaviours related to obesity

Abstract: Emotional and intuitive eating are associated with obesity. In the present study, it was aimed to evaluate the relationship between intuitive eating and emotional eating behaviours in adults with anthropometric measurements of obesity-related disease risk and gender. Body weight, body mass index (BMI), waist, hip and neck circumferences were taken. Emotional Eater Questionnaire and Intuitive Eating Scale-2 were used for the assessment of eating behaviour. A total of 3742 adult individuals (56⋅8 % (n 2125) fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…With respect to pg-BMI, we observed a negative influence on the overall IES-2 scale score. Other studies have also documented a higher level of intuitive eating with lower BMI [6,[15][16][17]20,22,41,42]. Among the postulated explanations for this inverse relationship is the hypothesis that the interoception and trust in hunger and satiety cues and less reliance on emotional or situational motivators to eat which are commonly observed with intuitive eating, positively influence food habits and the quantities of food consumed [43].…”
Section: Discussionmentioning
confidence: 94%
“…With respect to pg-BMI, we observed a negative influence on the overall IES-2 scale score. Other studies have also documented a higher level of intuitive eating with lower BMI [6,[15][16][17]20,22,41,42]. Among the postulated explanations for this inverse relationship is the hypothesis that the interoception and trust in hunger and satiety cues and less reliance on emotional or situational motivators to eat which are commonly observed with intuitive eating, positively influence food habits and the quantities of food consumed [43].…”
Section: Discussionmentioning
confidence: 94%
“…These associations were also observed between the three subscales—EPR, RHSC and B-FCC. In fact, obese individuals have less confidence in hunger and satiety signals, and eat less for physical reasons and more for emotional reasons, which explains why emotional eating is associated with increased body weight ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to highlight, however, that although intuitive eating is associated with a lower BMI ( 52 , 53 ), this way of eating is not capable of, in isolation, preventing weight gain, since this gain is multifactorial, and potentially greater in an adverse context, such as the pandemic ( 24–26 ). Thus, more intuitive eating may favor greater weight stability ( 12 ), and may, therefore, have helped to reduce the impact of the pandemic on weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…The authors believed this behavioural tendency to explain the link between poorer self‐reported interoceptive accuracy and higher BMI in a sample composed of 53% individuals with overweight and obesity (Robinson, Marty, et al., 2021). Among individuals with obesity, intuitive eating was found to be negatively correlated to body weight, BMI, emotional eating, waist‐height and waist‐hip ratios (Ayyıldız et al., 2023). Post‐bariatric surgery, intuitive eating was associated to weight loss (Nogué et al., 2019) and a healthier relationship with food (Virani et al., 2019).…”
Section: Introductionmentioning
confidence: 99%